2018
DOI: 10.1177/0022243718802853
|View full text |Cite
|
Sign up to set email alerts
|

Inspired to Create: Awe Enhances Openness to Learning and the Desire for Experiential Creation

Abstract: Automated fabrication, home services, and premade goods pervade the modern consumer landscape. Against this backdrop, this research explores how the emotion of awe might motivate a consumer to partake instead in experiential creation (i.e., activities in which they actively produce an outcome) by enhancing their willingness to learn. Across eight experiments, experiencing awe (vs. happiness, excitement, pride, amusement, or neutrality) increases people’s likelihood of choosing an experiential creation gift (vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 60 publications
1
52
0
2
Order By: Relevance
“…Awe is a unique and powerful emotion (Keltner and Haidt, 2003; Piff et al, 2015) that comprises three properties: (1) it conveys perceptual vastness – that is, the perception that something is immense in size, quantity, scope, complexity, ability, or social bearing (e.g., fame, authority) (Keltner and Haidt, 2003; Piff et al, 2015); (2) it conveys a need for accommodation – that is, the expansion of one’s general reference frame and the formation of a new cognitive structure in response to stimuli beyond one’s existing understanding of the world (Keltner and Haidt, 2003; Piff et al, 2015); and (3) it entails a thirst for innovation – that is, the increasing desire to explore new knowledge and experiences owing to frustration and loss of control when existing knowledge and psychological structure are challenged (Keltner and Haidt, 2003; Piff et al, 2015; Rudd et al, 2018). The sense of time abundance created by focusing on the present also increases people’s motivation to experience innovation (Keltner and Haidt, 2003; Rudd et al, 2012, 2018; Piff et al, 2015). Previous studies have shown that these specific functions of awe have significant effects on individual behaviors, such as an increasing willingness to help others, to donate, to participate in collective behavior, and to adopt pro-environment attitudes (Keltner and Haidt, 2003; Piff et al, 2015; Prade and Saroglou, 2016; Bai et al, 2017; Stellar et al, 2017; Jiang et al, 2018; Zhao et al, 2018).…”
Section: Awe and Green Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Awe is a unique and powerful emotion (Keltner and Haidt, 2003; Piff et al, 2015) that comprises three properties: (1) it conveys perceptual vastness – that is, the perception that something is immense in size, quantity, scope, complexity, ability, or social bearing (e.g., fame, authority) (Keltner and Haidt, 2003; Piff et al, 2015); (2) it conveys a need for accommodation – that is, the expansion of one’s general reference frame and the formation of a new cognitive structure in response to stimuli beyond one’s existing understanding of the world (Keltner and Haidt, 2003; Piff et al, 2015); and (3) it entails a thirst for innovation – that is, the increasing desire to explore new knowledge and experiences owing to frustration and loss of control when existing knowledge and psychological structure are challenged (Keltner and Haidt, 2003; Piff et al, 2015; Rudd et al, 2018). The sense of time abundance created by focusing on the present also increases people’s motivation to experience innovation (Keltner and Haidt, 2003; Rudd et al, 2012, 2018; Piff et al, 2015). Previous studies have shown that these specific functions of awe have significant effects on individual behaviors, such as an increasing willingness to help others, to donate, to participate in collective behavior, and to adopt pro-environment attitudes (Keltner and Haidt, 2003; Piff et al, 2015; Prade and Saroglou, 2016; Bai et al, 2017; Stellar et al, 2017; Jiang et al, 2018; Zhao et al, 2018).…”
Section: Awe and Green Consumptionmentioning
confidence: 99%
“…Previous studies have shown that these specific functions of awe have significant effects on individual behaviors, such as an increasing willingness to help others, to donate, to participate in collective behavior, and to adopt pro-environment attitudes (Keltner and Haidt, 2003; Piff et al, 2015; Prade and Saroglou, 2016; Bai et al, 2017; Stellar et al, 2017; Jiang et al, 2018; Zhao et al, 2018). In response to the increasing urgency for green development and Rudd et al (2018) call to advance research on awe, we extend the concept of awe to the current context of green consumption and posit that it will promote related green development behaviors; this is for several reasons.…”
Section: Awe and Green Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, unlike more self‐focused emotions (e.g., pride), awe makes people less focused on themselves and more connected to the world around them (Shiota et al., ). Moreover, in triggering a feeling of uncertainty and need for accommodation, awe also increases people's openness to learning (Rudd, Hildebrand, & Vohs, ) and motivates them to seek out order (e.g., by perceiving intentionality or patterns in randomness; Valdesolo & Graham, )—key ingredients in the facilitation of comprehension and, in turn, meaning.…”
Section: How To Spend Time In Ways That Enhance Meaningmentioning
confidence: 99%
“…Moreover, in triggering a feeling of uncertainty and need for accommodation, awe also increases people's openness to learning (Rudd, Hildebrand, & Vohs, 2018) and motivates them to seek out order (e.g., by perceiving intentionality or patterns in randomness; Valdesolo & Graham, 2014)-key ingredients in the facilitation of comprehension and, in turn, meaning.…”
Section: A Sense Of Comprehension: Connecting To the Worldmentioning
confidence: 99%